GAME DEVELOPMENT “GEMAS (MODIFIED DIVISION ENGKLEK GAME)” TO IMPROVE UNDERSTANDING OF CONCEPTSIN CLASS II ELEMENTARY SCHOOL STUDENTS - Annisa Amaliyatus Sofiyati; Ahmad Arifuddin; Wulan Andini (STAI Ma'had Aly Al-Hikam Malang, 2024)
This research aims to develop a game